Maximum likelihood self-calibration for direction-dependent gain-phase errors with carry-on instrumental sensors: case of deterministic signal model - Wang, Ding; Pan, Miao; Wu, Ying (Tongxin Xuebao, 2011)
Aim at the self-calibration of direction-dependent gain-phase errors in case of deterministic signal model, the maximum likelihood method(MLM) for calibrating the direction-dependent gain-phase errors with carry-on instrumental sensors was presented. In order to maximize the high-dimensional nonlinear cost function appearing in the MLM, an improved alternative projection iteration algorithm, which could optimize the azimuths and direction-dependent gain-phase errors was proposed. The closed-form expressions of the Cramer-Rao bound(CRB) for azimuths and gain-phase errors were derived. Simulation experiments show the effectiveness and advantage of the novel method.